Beneficial Health Effect of Aquarobics (Role of Adiponectin on Women with Obesity). (March 2017) - Baitul, M S; Susanto, H; Kushartanti, W; Soegiyanto; Rahayu, S
Abstract: Background the effects of exercise on adiponectin levels have been reported to be variable. Obesity is associated with adipose tissue inflammation and increased risk of infection. The prevalence of obesity increased in premenopausal women both in developed countries and developing countries, including Indonesia. The purpose of the study to investigate the effect of aquarobics exercise on adiponectin levels in women with obesity. Methods of the research, experimental randomized pretest-posttest control group design performed in twenty four women with obesity (Obese II BMI> 30kg/m2) aged 45-50 years, who were divided into 2 groups, aquarobic exercise group, twice days for 8 weeks (n=12), aquarobic intensity 75%HRmax, and control group (n=12). Percentage of body fat, BMI, adiponectin levels, blood glucose and lipids profile were measured before and after exercise. Data were analyzed using repeated measures and while Pearson's correlations were performed to identify possible relationship among the assessed variables. Results of the study, the percentage of body fat was higher in aquarobic exercises than control group (p<0.05). Decreased of BMI on the aquarobic exercises group compared to controls (p<0.05) and adiponectin levels in the aquarobic exercise group increase significantly (p<0.05). Conclusion: Aquarobic exercise is effective to decreased body weight and increase adiponectin levels.